On automated RBAC assessment by constructing a centralized perspective for microservice mesh - Das, Dipta; Walker, Andrew; Bushong, Vincent; Svacina, Jan; Cerny, Tomas; Matyas, Vashek (PeerJ. Computer science, 2021)
It is important in software development to enforce proper restrictions on protected services and resources. Typically software services can be accessed through REST API endpoints where restrictions can be applied using the Role-Based Access Control (RBAC) model. However, RBAC policies can be inconsistent across services, and they require proper assessment. Currently, developers use penetration testing, which is a costly and cumbersome process for a large number of APIs. In addition, modern applications are split into individual microservices and lack a unified view in order to carry out automated RBAC assessment. Often, the process of constructing a centralized perspective of an application is done using Systematic Architecture Reconstruction (SAR). This article presents a novel approach to automated SAR to construct a centralized perspective for a microservice mesh based on their REST communication pattern. We utilize the generated views from SAR to propose an automated way to find RBAC inconsistencies.
Keywords: REST; Static code analysis; Access control; Authorization; Security; Microservices; RBAC; Systematic architecture reconstruction